Comparison of power scheduling outcomes in electricity markets - Somboon Nuchprayoon (2018)
Power scheduling outcomes are observed through a comparison of three objective functions of power scheduling problem to reflect competition in electricity markets. Based on economic principles of nodal pricing, the optimal solutions of power scheduling problems are determined and analyzed. Sensitivity analysis and Monte Carlo simulations are employed to develop a framework for analyzing outcomes of power scheduling given that demand and cost data are private information. ©2009 IEEE.